PENYULUHAN PENCEGAHAN STUNTING MELALUI PEMBERIAN MAKANAN TAMBAHAN DARI OLAHAN IKAN PATIN - Olivia, Nina; Pratama, Muchti Yuda; Nisrina, Nisrina; Af’idah, Huwaina; Gustina, Erita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Stunting is caused by various factors, such as nutritional intake during pregnancy or infancy, lack of maternal knowledge about nutrition before or during pregnancy, and postpartum conditions that impact intelligence, susceptibility to diseases, and overall health. The provision of Supplementary Feeding (PMT) involves offering safe and high-quality snacks for toddlers, prioritizing food quality and safety. An innovative approach to addressing this issue involves utilizing local wisdom by processing catfish into cookies. This initiative was carried out at Posyandu Flamboyan, Jaharun B Village, Galang, Deli Serdang, involving 50 toddlers and their mothers attending the posyandu activities. The results showed that all toddlers experienced weight gain and enjoyed the cookies provided. Considering stunting is a serious issue, this program should be continued by encouraging local stakeholders to promote fish farming in the community and explore other catfish-based food innovations.